Crossing Routes: Artificial Intelligence Governance and Human Rights in Latin America - Llorens, María Pilar (2023)
Currently ongoing efforts are underway to develop normative frameworks for AI governance at different levels, including the Latin American region. These normative frameworks tend to highlight that the “respect and protection of human rights” should be at the core of AI development. However, the meaning of that expression remains to be explored. This work aims to understand the distinctive policy implications that arise for Latin American States when adopting a human centered approach to AI governance.